ATTENTION DEFICIT HYPERACTIVITY DISORDER E-SKOOL MOBILE APPLICATION - NAZLAN, NURIN NABILAH (IRC, 2020)
In this era of technology, the use of mobile application is no longer peculiar among by the people all over the world. Everything has been digitalized nowadays as people already becomes familiar with technology devices. Even education system also has introduced mobile learning education in the system. Nonetheless, most existing mobile application were created for the normal student used only and least for the special needs student. Hence, this mobile application is specially created for the special needs children especially Attention Deficit Hyperactivity Disorder children. Children with ADHD usually has a difficulty to stay focus especially on their studies. Thus, has led to slow learning performance as they need to learn one subtopic repeatedly to ensure they fully understand the topic and it is also very time consuming for them to master the topic. However, it is also depending on their moods and the attraction of the learning process itself. Therefore, ADHD E-Skool mobile application is created to help the student to gain their focus attention on the studies and also increase their learning performance. ADHD E-Skool will provide interactive learning module which is following the school syllabus. This application also focusses more on the animation and sounds as both components are important to attract ADHD children attention. Other than that, this application also provides user learning progress functionality where the teacher and parent can check on the children learning progress for every module.